Non‐canonical bivalent H3K4me3K9me3 recognition by Spindlin1/C11orf84 complex. (29th January 2022) - Du, Yongming; Qian, Chengmin
Abstract: Bivalent chromatin with active H3K4me3 and repressive H3K27me3 was initially identified in embryonic stem cells (ESCs) to poise expression of developmental genes upon lineage commitment. Since then, many more different bivalent modifications have been demonstrated in both ESCs and fully differentiated cells. Bivalency not only spatiotemporally controls gene transcription but also acts to fine‐tune the level of transcription during development. Although increasing number of studies demonstrated the functional significance of bivalent chromatin, the molecular connection of bivalent chromatin and transcriptional regulation remains largely elusive. Recently, we showed Spindlin1/C11orf84 complex prefers to recognize the non‐canonical histone H3K4me3K9me3 bivalent mark, which is required for timely ribosomal RNA transcription. Here, we hypothesize the recognition of K4me3 and K9me3 at the same histone tail by Spindlin1/C11orf84 complex may serve as a general mechanism of conversion from a repressed to an active chromatin structure for transcriptional activation. Abstract : The preferred recognition of non‐canonical bivalent H3K4me3K9me3 by Spindlin1/C11orf84 complex displaces HP1 from the silenced chromatin, which may facilitate the recruitment of KDM4A to demethylase H3K9me3 and eventually promote the conversion of bivalent H3K4me3K9me3 to the active H3K4me3 mark for transcriptional activation.